A review of physical experiments for leak detection in water pipes through transient tests for addressing future research - Brunone, Bruno; Maietta, Filomena; Capponi, Caterina; Keramat, Alireza; Meniconi, Silvia (Journal of hydraulic research, 2022)
Since the 1990s, pressure waves propagating in pressurized pipes during a transient event have been re-evaluated both in the laboratory and in real systems as a way to obtain information about location and size of leaks. However, a systematic analysis of the obtained results has not been offered yet in the literature. In this paper, a review of the available experimental data concerning the use of transient tests for leak identification in pressurized pipe systems is presented. The selected data are examined with regard to the main features (categories) influencing the transient response of a leaky pipe system: layout, modality of transient generation, material, diameter, pre-transient pressure and flow condition, inserted pressure wave, and leak characteristics. Moreover, for each of such categories, possible specific issues to address for future research are proposed.